Urban planning with respect to environmental quality and human well-being - Panagopoulos, Thomas (2017)
The cities of today present requirements that are dissimilar to those of the past. There are cities where the industrial and service sectors are in decline, and there are other cities that are just beginning their journey into the technological and industrial sectors. In general, the political and social realms have been restructured in terms of economics, which has resulted in an entirely different shape to the primitive structures of civilization. As people begin to understand the dynamic nature of landscapes, they stop seeing landscapes as a static scene. Sustainable cities must be simultaneously economically viable, socially just, politically well managed and ecologically sustainable to maximize human comfort. The present research suggests a multi-disciplinary approach for attaining a holistic understanding of urban environmental quality and human well-being in relation to sustainable urban development. (C) 2015 Elsevier Ltd. All rights reserved.